Ideal Banking Concept and Characteristics - Aithal, P S (International Research Journal of Management, IT & Social Sciences, 2016)
A bank is a financial intermediary and creates money by lending money to a borrower, thereby creating a corresponding deposit on the banks balance sheet. Lending activities can be performed directly by loaning or indirectly through capital markets. After the advent of technology and its penetration to all business fields, the responsibility of banks is enhanced to provide better, speedy, and ubiquitous service to the customers so that it can create more money and hence profit. Banks are formulating various strategies in order to attract more deposits and lend it to genuine customers to get a better return and hence make more profit. Based on such objective of a general banking system, the ideal concept of the banking system is developed. The ideal bank is a system with ideal banking characters.In this paper, a model of the ideal banking system is proposed by considering the ideal characteristics expected under input conditions, output conditions, system requirements, and environmental conditions. The factors affecting these characteristics are identified using a qualitative data collection instrument namely focus group method.